PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBENTUKVIDEO DENGAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION (RME) PADA MATA KULIAH MATEMATIKA SEKOLAH 2 - R. A. Rica Wijayanti (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2018)
Abstract: Mathematical learning media in the form of videos with a Realistic Mathematic Education (RME) approach was developed aimed at overcoming the problems experienced by mathematics education students in teaching school 2 mathematics courses which are compulsory subjects. In addition, this learning media in the form of videos is expected to increase students' learning motivation towards school 2 mathematics courses using science and technology. This type of research is Research and Development (R & D) research using the Borg & Gall development model. The stages carried out in this study were (1) initial research and data collection; (2) planning; (3) product draft development; (4) initial field trial; (5) revise the results of the trial; (6) field trials; (7) product improvement resulting from field tests; (8) field implementation test; (9) improvement of the final product; (10) dissemination and implementation. The data collection technique of this study uses the expert team validation sheet and user response questionnaire. The research data analysis used 2 analyzes namely descriptive statistical analysis and qualitative descriptive analysis. The results of the research that have been conducted show that the mathematics learning media in the form of videos with the Realistic Mathematic Education (RME) approach in school 2 mathematics courses are appropriate to be used by lecturers and students.